Solving System of Mixed Ordered Variational Inequalities Involving XOR and XNOR Operations in Ordered Product Banach Space - Ahmad, Iqbal; Farid, Mohammad; Irfan, Syed S. (Journal of Advances in Applied & Computational Mathematics, 2023)
In this article, we study a generalized system of mixed ordered variational inequalities problems with various operations in a real ordered product Banach space and discuss the existence of the solution of our considered problem. Further, we discuss the convergence analysis of the proposed iterative algorithm using XNOR and XOR operations techniques. Most of the variational inequalities solved by the projection operator technique but we solved our considered problem without the projection technique. The results of this paper are more general and new than others in this direction. Finally, we give a numerical example to illustrate and show the convergence of the proposed algorithm in support of our main result has been formulated by using MATLAB programming. 2010 AMS Subject Classification: 47H09; 49J40.